Potensi Daun Kelor (Moringa oleifera) Terhadap Kadar Kadmium Dan Kreatinin Dalam Darah Sebagai Indikator Kerusakan Fungsi Ginjal Pada Tikus Putih Yang Terpapar Asap Rokok - Christ Kartika Rahayuningsih; Riya Agustin; Tacik Idayanti (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2022)
High exposure of cigarettes in Indonesia causes various disturbances in the body's metabolism, especially in the kidney, which is due to the cadmium metal content. Cadmium induces oxidative stress by the formation of free radicals and decrease natural antioxidant activity in the kidney organs (nephrotoxic). One way to overcome nephrotoxic by decreasing blood creatinine, we can utilize Moringa oleifera (MO) which is known as a "miracle plant" and have high contents of flavonoid groups, phenols, gallic acid, ascorbic acid and carotenoids as antioxidants and natural metal chelating agents. This research aimed to analyze the potential of Moringa leaves in decreasing cadmium and creatinine levels in the blood of white rats due to exposure of cigarette smoke (inhalation) at doses 200, 400 and 800 mg/kgwb. The type of research was an experimental study with quantitative analysis conducted in October 2021 – July 2022. The independent variable was the doses of Moringa leaves extract and the dependent variable were the blood cadmium and creatinine levels of white rats. The blood cadmium level was measured with AAS and the creatinine level was measured with Jaffe method without deproteination by photometry. The results of blood cadmium and creatinine levels in the treatment of MO extract at dose 200 mg/kgwb were 1.288875 μg/L and 0.85 mg/dL; MO extract at dose of 400 mg/kgwb were 0.811 μg/L and 0.775 mg/dL; MO extract at dose 800 mg /kgwb were 0.86275 μg/L and 0.7 mg/dL. Based on statistical analysis using Kruskal wallis, the results of the p value on cadmium levels in the blood were 0.004 < 0.05 and the p value on creatinine levels was 0.003 < 0.05, showed that there were significant differences in blood cadmium and creatinine levels in the treatment groups. Moringa leaf extract (Moringa oleifera) at a dose of 400 mg/kgwb had good potential in overcoming kidney damage in terms of creatinine levels due to cadmium exposure through cigarette smoke, which was equivalent to 44.3756 grams of fresh Moringa leaves that can be implemented for human as an additional antioxidant for overcoming free radicals.                                                       Keywords : Moringa oleifera, Cigarettes Smoke, Cadmium, Creatinine, Rattus norvegicus